Physiological Sensing of Carbon Dioxide/Bicarbonate/pH via Cyclic Nucleotide Signaling - Buck, Jochen (Molecular Diversity Preservation International (MDPI), 2011)
Carbon dioxide (CO(2)) is produced by living organisms as a byproduct of metabolism. In physiological systems, CO(2) is unequivocally linked with bicarbonate (HCO(3)(−)) and pH via a ubiquitous family of carbonic anhydrases, and numerous biological processes are dependent upon a mechanism for sensing the level of CO(2), HCO(3), and/or pH. The discovery that soluble adenylyl cyclase (sAC) is directly regulated by bicarbonate provided a link between CO(2)/HCO(3)/pH chemosensing and signaling via the widely used second messenger cyclic AMP. This review summarizes the evidence that bicarbonate-regulated sAC, and additional, subsequently identified bicarbonate-regulate nucleotidyl cyclases, function as evolutionarily conserved CO(2)/HCO(3)/pH chemosensors in a wide variety of physiological systems.